Rape: Past and present legal regulation - Đapović Lasta S. (Glasnik Etnografskog Instituta SANU, 2002)
Rape was identified as a criminal act in the earliest known legal writings, Hamurabi's legal code (cir. 2000 BC). In the Balkans, in the Middle Ages, rape was always punished in one way or another, in the statutes of the Adriatic maritime towns, which were under the rule of the Nemanjić state or the West. All categories of women, even prostitutes and slaves, were protected by law from sexual violence in many statutes. Also in Dušan's legal code the regulation is found, severely punishing rapists. Laws following the Second Serbian Uprising, also provide severe punishment for sexual violence, especially towards women but also male minors. Legal and court practice, following the Second World War, indicate that the protection of women from sexual violence is completely inadequate and this at a time when women had achieved equal rights with men in many spheres of life. World events at the end of the 20th century: collapse of the Soviet Union: as well as the happenings in this region,: war, ethnic and religious conflicts resulted in massive rape of women, opening of brothels, trading women and family violence. Non state organizations, mainly women in expert associations, invest great effort to rectify this very unsatisfactory situation. They exert pressure for change in the law and in court practice, by which women would have more effective defense against sexual violence, as well as organized assistance for women victims of traffic, and warning of the possible danger.